Exchange-rate misalignments in duopoly: the case of Airbus and Boeing - Agnès Bénassy-Quéré; Lionel Fontagné; Horst Raff (Kiel Institute for the World Economy (IfW), 2009)
We examine the effect of exchange-rate misalignments on competition in the market for large commercial aircraft. This market is a duopoly where players compete in dollar-denominated prices while one of them, Airbus, incurs costs mostly in euros. We construct and calibrate a simulation model to investigate how companies adjust their prices to deal with the effects of a temporary misalignment, and how this affects profit margins and volumes. We also explore the effects on the long-run dynamics of competition. We conclude that due to the duopolistic nature of the aircraft market, Airbus will pass only a small part of the exchange-rate fluctuations on to customers through higher prices. Moreover, due to features specific to the aircraft industry, such as customer switching costs and learning-by-doing, even a temporary departure of the exchange rate from its long-run equilibrium level may have permanent effects on the industry.
Keywords: F31; L13; 330; Exchange rates; pass-through; oligopoly; Luftfahrtindustrie; Duopol; Exchange Rate Pass-Through; Internationaler Wettbewerb; Theorie; EU-Staaten; USA